2014
DOI: 10.1097/icu.0000000000000013
|View full text |Cite
|
Sign up to set email alerts
|

Laser-assisted cataract surgery

Abstract: The FSL may significantly change the current approach to cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 23 publications
1
21
0
1
Order By: Relevance
“…11 Hatch et al recently illustrated the potential advantages of FLACS in brunescent cataracts, Fuchs endothelial dystrophy, pseudoexfoliation or those with a history of trauma; 83 however, additional studies are awaited to establish a definitive advantage.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 98%
See 1 more Smart Citation
“…11 Hatch et al recently illustrated the potential advantages of FLACS in brunescent cataracts, Fuchs endothelial dystrophy, pseudoexfoliation or those with a history of trauma; 83 however, additional studies are awaited to establish a definitive advantage.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 98%
“…83 Other contraindications include as central corneal scarring in the area of the laser delivery zone, non-transparent corneal inlays (There has been a case report of use in a transparent inlay 135 ) and corneal bullae.…”
Section: Victus Femtosecond Laser Platform (Bausch and Lomb Rochestementioning
confidence: 98%
“…1 Recently, it was reported that the best-case scenario of femtosecond laser cataract surgery with excellent visual outcomes (100%), a significant reduction in complications (0%), and a significantly reduced cost to patient (of $300) would result in reasonable incremental cost-effectiveness ratios. 28 From the point of view of ophthalmology practice, the learning curve is short and intraoperative complications can be avoided, 3 especially for difficult cases of Fuchs' endothelial dystrophy, pseudoexfoliation, brunescent cataracts, 29 and trauma. 30 The flexibility, real-time intraoperative visualization, and ease of use ensure rapid progress in practice.…”
Section: Visual and Refractive Outcomesmentioning
confidence: 99%
“…9 Etkili lens pozisyonu (ELP), özellikle multifokal GİL'ler için çok önemli olup, bu grupta reksisin büyüklüğü ve konumu özellikle önem arz etmektedir. 10,11 Mihalltz ve ark., FSL ile uygulanan kapsüloto-mili gözleri manuel yöntemle karşılaştırdığında, internal aberasyonların lazer grubunda daha az olduğunu ve optik kalite açısından daha avantajlı olduğunu göstermişlerdir. 12 Dick ve Schultz, lazer sistemi kullanarak yaptıkları çalışmada, son ELP'nin lazer sistemi ile hemen elde edilebildiğini ve daha ön görülebilir refraktif sonuçlara ulaşıldığını göstermişlerdir.…”
Section: öN Kapsülotomi̇unclassified